2016
DOI: 10.4055/cios.2016.8.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality in Nonagenarians Following the Surgical Repair of Hip Fractures

Abstract: BackgroundThe purpose of this study is to report on the mortality of nonagenarians who underwent surgical treatment for a hip fracture, specifically in regards to preexisting comorbidities. Furthermore, we assessed the effectiveness of the Deyo score in predicting such mortality.MethodsThirty-nine patients over the age of 90 who underwent surgical repair of a hip fracture were retrospectively analyzed. Twenty-six patients (66.7%) suffered femoral neck fractures, while the remaining 13 (33.3%) presented with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…A recent study investigating factors affecting mortality in patients 90 years of age has found higher hazard ratios for mortality in patients with congestive heart failure and chronic obstructive pulmonary disease. 8 differs from this conclusion in this study. In this study, author found that the co-morbidity in the preoperative period was not effective on mortality rates.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…A recent study investigating factors affecting mortality in patients 90 years of age has found higher hazard ratios for mortality in patients with congestive heart failure and chronic obstructive pulmonary disease. 8 differs from this conclusion in this study. In this study, author found that the co-morbidity in the preoperative period was not effective on mortality rates.…”
Section: Resultscontrasting
confidence: 99%
“…In a recent study by Aschraf et al, they examined hip fractures in patients 90 years of age and older and gave similar mortality rates as the results (10.3% in hospital, 20.5% in 3 months and 35.9% in 1 year). 8 In this study, author found in-hospital mortality rate as 8.4% (n:7), 3month mortality rate as 18.1% (n:15), and 1-year mortality as 25.3% (n:21). In a study conducted by Lin et al, they found a mortality rate of 9.9%, which is similar to the in-hospital mortality rate in this study.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The presence of several comorbidities shown to be associated with poor outcomes in patients with hip fracture were adjudicated from electronic patient charts: dementia, 1,3,9,12,16,17 congestive heart failure (CHF), 26,27 chronic kidney disease (CKD), [28][29][30] and depression. 31 Each condition was recognized as present if cited in the patient's problem lists or physician notes.…”
Section: Comorbiditiesmentioning
confidence: 99%